Effects of bilirubin on the development and electrical activity of neural circuits - Wu, Cuiping; Jin, Yuefan; Cui, Yaqi; Zhu, Yidan; Yin, Shankai; Li, Chunyan (Frontiers in Cellular Neuroscience, 2023)
In the past several decades, bilirubin has attracted great attention for central nervous system (CNS) toxicity in some pathological conditions with severely elevated bilirubin levels. CNS function relies on the structural and functional integrity of neural circuits, which are large and complex electrochemical networks. Neural circuits develop from the proliferation and differentiation of neural stem cells, followed by dendritic and axonal arborization, myelination, and synapse formation. The circuits are immature, but robustly developing, during the neonatal period. It is at the same time that physiological or pathological jaundice occurs. The present review comprehensively discusses the effects of bilirubin on the development and electrical activity of neural circuits to provide a systematic understanding of the underlying mechanisms of bilirubin-induced acute neurotoxicity and chronic neurodevelopmental disorders.